Positioning of New Beaches in Bali: The Perspective of Tourist - Eprisandi, Ni Kadek Monika; Kristiono Listiandre, Hanugerah; Made Subrata, I (Green Publisher Indonesia, 2024)
Beach in Bali are one of the main attractions of the island's tourism. The beauty of Bali's beaches, with their clean white sand, clear sea water, and ideal surfing waves, makes them famous. Each beach has unique characteristics that can be used as a competitive advantage to help tourists choose their destination in Bali. This study uses Multidimensional Scaling and Correspondence Analysis techniques to identify the advantages of each attribute for tourists. The results show that Diamond Beach's position as a tourist destination is similar to Green Bowl Beach. Based on the evaluation of fifteen items by respondents, it is evident that Diamond Beach has a diverse range of positive perceptions. Diamond Beach excels in attributes such as beach safety, sand color, and cleanliness.